Spatial diversification of musculoskeletal and connective tissue incidence of Polish population - Agnieszka Anna Pilarska (Journal of Education, Health and Sport, 2018)
Introduction: Musculoskeletal and connective tissue disorders, which can be classified as civilization diseases, constitute an important element of a comprehensive analysis of health condition of people aged over 19. A comprehensive analysis of this component should not overlook the spatial aspect, i.e. the question of spatial diversification. Aim of the paper: The purpose of the paper was presented in the article’s title. It is an analysis of spatial diversification of the musculoskeletal and connective tissue disorder incidence by voivodeships and districts (poviats). Materials and methods: In the paper, data from the following organisations were used: Centrum Systemów Informacyjnych Ochrony Zdrowia (CSIOZ) [Centre of Health Information Systems], Bank Danych Lokalnych Głównego Urzędu Statystycznego (BDL GUS) [Local Data Bank of Central Statistical Office], Centralny Ośrodek Dokumentacji Geodezyjnej i Kartograficznej (CODGiK) [National Surveying and Cartographic Documentation Centre] and from “Natural Earth. Free vector and raster map data”. Within the scope of the paper, the crude incidence rate was calculated and choropleth maps were developed constituting a cartographic visualization of the calculated rates. Results: The results of the carried out analysis were presented in the form of the cartographic visualisation and tables including change dynamics. It constituted the basis for identification of the areas of advantageous and disadvantageous epidemiological situation. Conclusions: In light of the obtained results, among other things, the following has to be stated: the areas of disadvantageous epidemiological situation include northern Poland and some of the former Russian partition voivodeships